Replication and mutagenesis of UV-damaged DNA templates in human and monkey cell extracts. - Carty, M P (1993)
We have used in vitro DNA replication systems from human HeLa cells and monkey CV-1 cells to replicate a UV-damaged simian virus 40-based shuttle vector plasmid, pZ189. We found that replication of the plasmid was inhibited in a UV fluence-dependent manner, but even at UV fluences which caused damage to essentially all of the plasmid molecules some molecules became completely replicated. This replication was accompanied by an increase (up to 15-fold) in the frequency of mutations detected in the supF gene of the plasmid. These mutations were predominantly G:C-->A:T transitions similar to those observed in vivo. Treatment of the UV-irradiated plasmid DNA with Escherichia coli photolyase to reverse pyrimidine cyclobutane dimers (the predominant UV-induced photoproduct) before replication prevented the UV-induced inhibition of replication and reduced the frequency of mutations in supF to background levels. Therefore, the presence of pyrimidine cyclobutane dimers in the plasmid template appears to be responsible for both inhibition of replication and mutation induction. Further analysis of the replication of the UV-damaged plasmid revealed that closed circular replication products were sensitive to T4 endonuclease V (a pyrimidine cyclobutane dimer-specific endonuclease) and that this sensitivity was abolished by treatment of the replicated DNA with E. coli photolyase after replication but before T4 endonuclease treatment. These results demonstrate that these closed circular replication products contain pyrimidine cyclobutane dimers. Density labeling experiments revealed that the majority of plasmid DNA synthesized in vitro in the presence of bromodeoxyuridine triphosphate was hybrid density whether or not the plasmid was treated with UV radiation before replication; therefore, replication of UV-damaged templates appears to occur by the normal semiconservative mechanism. All of these data suggest that replication of UV-damaged templates occurs in vitro as it does in vivo and that this replication results in mutation fixation.